Transmembrane pH of Clostridium acetobutylicum is inverted (more acidic inside) when the in vivo activity of hydrogenase is decreased. - Girbal, L (1994)
Evidence is reported here that alkalinization of Clostridium acetobutylicum cytoplasm involves hydrogenase activity. A decrease of in vivo hydrogenase activity is accompanied by intracellular accumulation of protons leading to a negative (interior acidic) pH gradient. However, the organism is able to maintain a constant proton motive force by interconverting chemical and electrical potentials.